ANALYSIS OF FACTORS AFFECTING THE IMPLEMENTATION OF COMPUTER-BASED ACCOUNTING INFORMATION SYSTEM ON SMALL AND MEDIUM ENTERPRISES - Siti Nur Azizah (Universitas Muhammadiyah Yogyakarta, 2017)
The objective of the research is to examine some factors that influence implementation computer-based accounting information system on Small and Medium Enterprises (SMEs). The study is based on the model proposed by Davis (1989), they are perceived usefulness, perceived ease of use, the attitude toward using, intention in use and actual usage that includes in Technology Acceptance Model (TAM) theory. Computer-based accounting information system in this study was measured by usage of Point of Sales (POS) system. This study used data obtained from individual perception of information system user in Dieng-Mart Swalayan collected from 33 questionnaires. The data were analyzed by regression use SPSS 16.0 software.  Study result shows that the implementation of Computer-based accounting information system is influenced by perceived ease of use and attitude toward using which are included in TAM theory.